PENGUJIAN KARAKTERISTIK UJI IMPACT MATERIAL KOMPOSIT MATRIKS RESIN POLYESTER CAMPUR SERAT PISANG DAN PASIR BESI DENGAN VARIASI BERAT - Agrippina Fa'iz; Fery Setiawan; Edi Sofyan (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
The development of composite materials is increasingly rapid to obtain alternative materials that meet the criteria, namely the material is strong, light, cheap and easy to obtain. In this study, banana fiber and iron sand were chosen because of their abundance in Indonesia, so they are easy to obtain. The specimens were made using the hand layup method with woven fiber grooves, polyester resin was used as a specimen matrix, specimen testing used charpy impact testing to determine strength, hardness, and ductility. The purpose of the study was to find out the best composition of the variations of the specimens made. experimental method was used with a ratio of four weight variations (0%, 20%, 30%, 40%). In specimens with a weight fraction of 0% the value of absorption energy (0.961 J/mm2) and impact values ​​(0.0080 J/mm2), the highest value for the 10% weight fraction was sample A (0.0043 J/mm2) and the highest value was in sample A (0.0043 J/mm2). The lowest value was in the B fraction (0.004 J/mm2), the 20% weight fraction specimen, the highest value was in the B sample (0.0033 J/mm2) and the lowest value was in the A and C samples (0.0025 J/mm2), the heavy fraction specimen 30% of the highest value is in sample B (0.0025 J/mm2) and the lowest value is in samples A and C (0.0019 J/mm2), of the four weight variations the highest value of impact testing results is 10% fiber volume with a value of 0 .0043 J/mm2 and the lowest value is 100% fiber volume with a value of 0.0012 J/mm2